Posture evaluation of the automotive maintenance workers: a case study - Shukriah Abdullah,; Nor Kamaliana Khamis,; Jaharah A. Ghani,; Kurniawan, Rudi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Automotive maintenance workers or commonly known as mechanics are exposed to numerous work stressors while performing their works. Maintenance activities required worker to be in different type of working posture, which mostly awkward posture and in high risk to developed musculoskeletal disorder. Statistics data disclosed that musculoskeletal disorder among maintenance workers is quite high compared to the other types of job sectors. Therefore, this study aims to examine the working posture amongst the mechanics based on their job activities. By using an ergonomic assessment sheet for posture known as Rapid Entire Body Assessment (REBA), ten common vehicle maintenance activities with ten mechanic in the maintenance jobs have been evaluated based on their feedback. The findings showed that, nine out of ten activities are in the high risk and necessary action need to be taken soon. Awkward posture such as excessive bending and twisting for several body parts with heavy parts as well as poor coupling design on the automotive parts or tools are the factors that influence the risk of injury in this maintenance activities. This study is very useful for automotive industry to evaluate their worker’s condition in maintenance activities. This should be an employer and employee essential knowledge to understand that vehicle maintenance work will include awkward posture. Self-awareness regarding the high risk in developing musculoskeletal disorder will reduce the worker chance to be in discomfort while working.